Polymer additive as well as preparation method and application thereof
By using crosslinked polymer additives formed by click polymerization in perovskite light emitting diodes, the problem of insufficient operation stability of traditional PeLEDs is solved, and significant half-life extension and performance improvement is achieved.
Patent Information
- Application Number
- CN202411983288.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional perovskite light-emitting diodes (PeLEDs) have insufficient operating stability and short half-life, which cannot meet the needs of actual application, mainly due to device instability caused by ion migration.
A crosslinked polymer formed by click polymerization reaction is used as an additive, and it is directly added to the perovskite preparation raw material. The crosslinked polymer network formed by click polymerization reaction occurs through the monomer to effectively inhibit ion migration, and fill and coat the perovskite grain boundaries through a 3D network structure to improve the moisture isolation, mechanical force and thermal resistance of the device.
It significantly improves the operating stability of perovskite light-emitting diodes, extends the half-life, and improves the performance and application prospects of the device.
Smart Images

Figure CN119798652A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite materials, and specifically relates to a polymer additive and a preparation method and application thereof. Background Art
[0002] Thanks to the excellent semiconductor optoelectronic properties, optoelectronic devices based on perovskite materials have developed rapidly in the past decade. Specifically for light-emitting applications, perovskite materials have the characteristics of easy processing, high luminescence quantum yield, narrow luminescence spectrum, low cost, and compatibility with flexible structures, which makes them a strong competitor for the next generation of light-emitting diode technology. At present, the external quantum efficiency of perovskite light-emitting diodes (PeLEDs) has exceeded 20%, meeting the needs of current commercial applications. However, in terms of operational stability, the half-life (T50) of traditional PeLEDs can only reach about 160 minutes. Because perovskite is an ionic crystal material, on the one hand, the wet processing technology of perovskite materials leads to a large number of defects in its film, especially anion vacancies and unsaturated B-site cations, which provide corresponding sites for ion migration. Among them, the grain boundary is the most important channel for ion migration. On the other hand, PeLEDs need to work under an electric field, which provides "power" for ion migration. Therefore, for PeLEDs, the ion migration process cannot be avoided. In order to improve the operational stability of the device, it is usually focused inside the perovskite film layer to suppress ion migration as much as possible to improve the device half-life.
[0003] Additive engineering is an effective method to directly reach the interior of the perovskite film layer, using the coordination interaction between additives and perovskites to anchor and enrich at the grain boundaries. On the one hand, it passivates grain boundary defects and reduces the source of ion migration; on the other hand, it fills the grain boundaries and inhibits the penetration of "harmful" factors such as external moisture / oxygen. Currently, conventional additives mainly include inorganic salts. However, the existing additive systems are difficult to effectively improve the operational stability of PeLEDs. The half-life (T50) of PeLEDs is still at the level of tens of hours, which is far lower than the requirements of practical applications. To a certain extent, it limits the development and application of perovskite light-emitting diodes. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a polymer additive, which can be used in perovskite light-emitting diodes to significantly increase the diode half-life and has good application prospects.
[0005] The invention also provides a preparation method of the polymer additive.
[0006] The invention also provides a method for preparing the perovskite material.
[0007] The invention also provides a perovskite material.
[0008] The invention also provides a photoelectric device.
[0009] The present invention also proposes the use of the above polymer additive or perovskite material in the preparation of optoelectronic devices.
[0010] In the first aspect of the present invention, a polymer additive is proposed, including a cross-linked polymer formed by a click polymerization reaction of monomers after being added to a raw material for preparing perovskite, wherein the type of click polymerization reaction includes at least one of amino-alkynyl click polymerization, thiol-alkynyl click polymerization, thiol-alkynyl click polymerization, hydroxyl-alkynyl click polymerization, and Diels-Alder click polymerization.
[0011] The polymer additive according to the embodiment of the present invention has at least the following beneficial effects:
[0012] The polymer additive of the present invention includes a cross-linked polymer obtained by a click polymerization reaction of a monomer after being added to the raw material for preparing perovskite, and has a cross-linked polymer network (3D network structure), which can effectively inhibit ion migration, greatly improve the operational stability of perovskite and perovskite devices, and can also provide better filling and coating for perovskite grain boundaries and grains through its own 3D mesh structure, so as to achieve better moisture isolation, mechanical force and thermal resistance. The peripheral groups of the cross-linked polymer further passivate defects and slow down the erosion of water on grain boundaries by interacting with the surface of the perovskite material. And the additive in the present invention can directly reach the inside of the perovskite film, which has the advantages of simple process, high process compatibility and controllable cost.
[0013] In addition, cross-linked polymers may be insoluble under certain conditions and difficult to be used directly as additives. In the present invention, the monomers can be directly added to the raw materials for perovskite preparation, and metal-free catalytic click polymerization (such as amino-alkyne-free metal-catalyzed click polymerization monomers) can be achieved. In addition, it is an in-situ cross-linking method for click polymerization, and the preparation method is simple. No catalyst is required during the cross-linking process, which avoids the quenching effect of the catalyst on the luminescence of perovskite. That is, the present invention can realize the in-situ cross-linking strategy of metal-free catalytic click polymerization such as amino-alkyne, directly using cross-linkable alkyne-containing monomers and amino-containing monomers as raw materials for additives, and forming a continuous network structure through in-situ polymerization of monomers, while protecting grain boundaries and passivating defects, effectively blocking ion migration, and achieving a significant improvement in the operational stability of PeLEDs.
[0014] In some embodiments of the present invention, the monomer includes an acetylene compound I with a functionality of 2 or more and an amine compound II with a functionality of 2 or more, and the sum of the functionalities of the acetylene compound I and the amine compound II is 5 or more; or / and, the monomer includes a monomer compound III containing both an acetylene group and an amine group, and the sum of the functionalities of the acetylene group and the amine group in the monomer compound III is 3 or more. Optionally, the acetylene compound I contains more than 2 acetylene groups, and the amine compound II contains more than 2 amine groups, and the sum of the number of acetylene groups contained in the acetylene compound I and the number of amine groups contained in the amine compound II is greater than 5. Optionally, the sum of the number of acetylene groups and amine groups in the monomer compound III is 3 or more. In some embodiments of the present invention, the amine group is a secondary amine group.
[0015] In some embodiments of the present invention, the functionality of the acetylene compound I is 3 or more, and the functionality of the amine compound II is 2 or more; or, the functionality of the acetylene compound I is 2 or more, and the functionality of the amine compound II is 3 or more. Optionally, the number of acetylene groups contained in the acetylene compound I is 3 or more, and the number of amine groups contained in the amine compound II is 2 or more; or, the number of acetylene groups contained in the acetylene compound I is 2 or more, and the number of amine groups contained in the amine compound II is 3 or more.
[0016] Through the above implementation, the additive monomer forms a cross-linked polymer to improve the performance of perovskite and perovskite device operation stability.
[0017] In some embodiments of the present invention, the acetylene compound I is a trifunctional acetylene compound, and the amine compound II is a difunctional amine compound; or, the acetylene compound I is a difunctional acetylene compound, and the amine compound II is a trifunctional amine compound.
[0018] In some embodiments of the present invention, the acetylene compound I comprises at least one of the following compounds:
[0019]
[0020] Wherein, R1 and R2 are independently selected from C1 to C 10 Alkyl, C1~C 10 Alkoxy;
[0021] p, q, r, and t are all integers, and p is selected from 2 to 20, q and r are independently selected from 0 to 8 each time they occur, and t is independently selected from 2 to 10 each time it occurs.
[0022] In some embodiments of the present invention, R1 and R2 are independently selected from C1-C5 alkyl and C1-C5 alkoxy. Alternatively, R1 and R2 are independently selected from methyl, ethyl or propyl.
[0023] In some embodiments of the present invention, the amino compound II comprises at least one of the following compounds:
[0024]
[0025] Wherein, each occurrence of R3 is independently selected from C1 to C 10 Alkyl, C1~C 10 Alkoxy;
[0026] m, n, k, s, and w are all integers, and m and n are independently selected from 2 to 8 each time they occur, k is independently selected from 2 to 6 each time it occurs, s is independently selected from 0 to 8 each time it occurs, and w is independently selected from 2 to 18 each time it occurs.
[0027] In some embodiments of the present invention, the compound B6 comprises at least one of the following compounds:
[0028]
[0029] In some embodiments of the present invention, the monomer compound III includes more than 2 amine groups and more than 3 alkynyl groups, or the monomer compound III includes more than 3 amine groups and more than 2 alkynyl groups.
[0030] In some embodiments of the present invention, the monomer compound III comprises at least one of the following compounds:
[0031]
[0032] a and b are both integers, and each occurrence of a and b is independently selected from 0 to 8.
[0033] In some embodiments of the present invention, the molecular weight of the polymer additive is 3k-100k.
[0034] The second aspect of the present invention provides a method for preparing a polymer additive, comprising the following steps: mixing an additive preparation raw material containing a monomer and a solvent with a perovskite preparation raw material, heating, and performing a click polymerization reaction to obtain a polymer additive.
[0035] In some embodiments of the present invention, the solvent includes but is not limited to one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and the like.
[0036] In some embodiments of the present invention, the solvent includes N,N-dimethylformamide and dimethyl sulfoxide. Optionally, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (1-10):1.
[0037] In some embodiments of the present invention, the heating temperature is 40-100°C, such as 40-80°C.
[0038] Through the above-mentioned embodiments, the click polymerization reaction such as amino-alkyne in the present invention has a mild and efficient reaction temperature. When the monomer of the polymer additive is used as a raw material to generate the polymer additive in the perovskite precursor by adopting an in-situ polymerization strategy, it is very beneficial for the raw material of the polymer additive to fully react in the subsequent thermal annealing process (heating) of the perovskite light-emitting diode, avoiding the damage of the reaction residue to the photoelectric performance of the perovskite device, and having a good application prospect. For example, in some embodiments of the present invention, the perovskite light-emitting diode can realize a 40°C annealing process, and the perovskite crystal quality is not attenuated.
[0039] In some embodiments of the present invention, the heating time is 5 to 300 minutes, such as 15 to 80 minutes.
[0040] In some embodiments of the present invention, the raw materials for preparing the additive are the monomer and the solvent. The monomer cross-linking process of the present invention does not require a catalyst, thereby avoiding the quenching effect of the catalyst on the luminescence of the perovskite; the additive engineering can directly reach the interior of the perovskite film, and has the advantages of simple process, high process compatibility, and controllable cost.
[0041] In some embodiments of the present invention, the monomer includes acetylene compound I and amino compound II. Optionally, the mass ratio of acetylene compound I to amino compound II is 1:(0.2-5), such as 1:(0.9-1.2).
[0042] The third aspect of the present invention provides a perovskite material comprising the above-mentioned polymer additive.
[0043] In some embodiments of the present invention, the perovskite material further comprises perovskite.
[0044] In some embodiments of the present invention, the mass ratio of the perovskite to the polymer additive is 100:(0.1-15), such as 100:(3-10).
[0045] In some embodiments of the present invention, the perovskite includes but is not limited to one or more of MAPbBr3, FAPbBr3, CsPbBr3, MAPbI3, FAPbI3, CsPbI3, MAPbCl3, FAPbCl3, CsPbCl3, mixed cation perovskite, mixed anion perovskite, quasi-two-dimensional perovskite, etc.
[0046] In a fourth aspect of the present invention, a method for preparing a perovskite material is proposed, comprising the following steps: taking a raw material for preparing perovskite and a raw material for preparing a polymer additive containing a monomer and a solvent, mixing, and annealing to obtain the perovskite material.
[0047] The method for preparing the perovskite material according to the embodiment of the present invention has at least the following beneficial effects:
[0048] Generally, thermal annealing is one of the essential processes in the preparation of perovskite devices. Through annealing, the perovskite grains are induced to achieve better growth, and a large-grained, uniform, and dense perovskite film layer is obtained. Usually, the annealing temperature of perovskite devices exceeds 100°C. The purpose is to quickly induce the formation of a large number of crystal nuclei through a high temperature, so as to achieve a more orderly growth of subsequent grains.
[0049] The present invention has a mild and efficient reaction temperature (e.g., 40-80°C) through metal-free catalytic click polymerization such as amino-alkynyl. Due to this, polymer additive monomers such as amino-alkynyl monomers rapidly undergo metal-free catalytic click polymerization to form a three-dimensional network structure, which divides the perovskite precursor solution into countless small sections in space. The perovskite is bound in this small "grid" and is slowly crystallized to form a dense perovskite material (e.g., a thin film material) with relatively uniform grain size.
[0050] The monomers of the present invention can form a cross-linked network in situ and efficiently in the subsequent process flow (such as annealing); the cross-linking reaction of the monomers is specific, the perovskite does not affect the polymerization, and the monomers do not participate in the crystallization; the cross-linking reaction conditions are mild, because the perovskite ion migration is a strongly temperature-dependent process, high temperature will induce a large degree of ion migration, and the lower temperature in the present invention greatly reduces the ion migration; and the monomer design is flexible, and heteroatoms containing lone pairs of electrons such as O, S, and N can be easily introduced to interact with the perovskite in a coordinated manner; and the cross-linking process can be achieved without a catalyst, thereby avoiding the quenching effect of the catalyst on the perovskite luminescence.
[0051] The perovskite material prepared by the present invention has uniform thickness, dense and uniform surface morphology, and the corresponding perovskite light-emitting diode device has good performance. At the same time, the cross-linked polymer formed by the metal-free catalytic click polymerization reaction such as amino-alkyne monomers in the present invention fully fills the gaps between the perovskite grains, thereby achieving tight wrapping and protection of the perovskite grains. The mild annealing temperature greatly reduces the difficulty and complexity of the process, and at the same time increases the thermal stability selection window of the available materials.
[0052] That is, the present invention proposes an in-situ crosslinking strategy such as amino-alkyne-free metal-catalyzed click polymerization, directly adding crosslinkable alkyne monomers and amine monomers, and forming a continuous network structure through in-situ polymerization of the monomers, while protecting the grain boundaries and passivating defects, effectively blocking ion migration, thereby significantly improving the operational stability of perovskite and corresponding devices (PeLEDs). The crosslinked polymer additive polymer of the perovskite material of the present invention has a 3D network structure, which has better moisture isolation, mechanical strength and thermal resistance.
[0053] In some embodiments of the present invention, the solvent includes but is not limited to at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and the like.
[0054] In some embodiments of the present invention, the solvent includes N,N-dimethylformamide and dimethyl sulfoxide. Optionally, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (1-10):1.
[0055] In some embodiments of the present invention, the annealing temperature is 40-100°C, such as 40-80°C.
[0056] In some embodiments of the present invention, the annealing time is 5 to 300 minutes, such as 15 to 80 minutes.
[0057] In some embodiments of the present invention, the raw materials for preparing the perovskite include PbX2 and BX, wherein X is independently selected from at least one of F, Cl, Br or I each time it appears; and B is selected from at least one of MA, FA or Cs.
[0058] In some embodiments of the present invention, the molar ratio of PbX2 to BX is 1:(0.8-1.5), such as 1:(1-1.3).
[0059] In some embodiments of the present invention, the ratio of the raw materials for preparing the perovskite to the solvent is 5 to 15 mol:1L.
[0060] In some embodiments of the present invention, the monomer includes acetylene compound I and amino compound II. Optionally, the mass ratio of acetylene compound I to amino compound II is 1:(0.2-5), such as 1:(0.9-1.2).
[0061] In some embodiments of the present invention, the preparation method comprises:
[0062] S1, mixing a raw material for preparing perovskite, a monomer and a solvent to obtain a mixture;
[0063] S2, coating the mixture on a substrate surface and annealing to obtain the perovskite material.
[0064] In some embodiments of the present invention, the perovskite material is a perovskite material layer.
[0065] In some embodiments of the present invention, the thickness of the perovskite material layer is 2 to 300 nm, such as 20 to 150 nm.
[0066] According to a fifth aspect of the present invention, a photoelectric device is provided, comprising the above-mentioned perovskite material.
[0067] The polymer additive and perovskite material obtained by in-situ crosslinking of metal-free click polymerization monomers in the present invention can be applied to perovskite devices such as perovskite light-emitting diodes to improve their operational stability and greatly promote their commercialization process and application, including but not limited to applications in the fields of semiconductor display, lighting, optical communication, etc. In addition, the polymer additive and perovskite material of the present invention can also be applied to perovskite photoelectric devices such as perovskite color film, perovskite laser, perovskite detector, and perovskite scintillator that suffer from operational stability problems.
[0068] In some embodiments of the present invention, the optoelectronic device includes at least one of a perovskite color film or a perovskite scintillator; the perovskite color film includes the perovskite material, and the perovskite scintillator includes the perovskite material.
[0069] In some embodiments of the present invention, the optoelectronic device includes at least one of a perovskite light emitting diode, a perovskite laser, and a perovskite detector.
[0070] In some embodiments of the present invention, the perovskite light-emitting diode comprises a perovskite material layer, and the perovskite material layer comprises the perovskite material.
[0071] In some embodiments of the present invention, the perovskite light-emitting diode includes a substrate, a hole transport layer, a perovskite material layer, an electron transport layer, an electrode modification layer and an electrode which are stacked in sequence.
[0072] The sixth aspect of the present invention proposes the use of the above-mentioned polymer additive or perovskite material in the preparation of optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0074] Figure 1 This is a microscopic test result diagram of the perovskite material layer of the diode in Comparative Example 1;
[0075] Figure 2 This is a diagram showing the microscopic test results of the perovskite material layer of the diode in Example 1 of the present invention;
[0076] Figure 3 This is a diagram showing the stability test results of the perovskite light-emitting diode in Example 1 of the present invention;
[0077] Figure 4 This is a graph showing the stability test results of the perovskite light-emitting diode in Comparative Example 1. DETAILED DESCRIPTION
[0078] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0079] The experimental methods without specific conditions in the following examples and comparative examples are generally based on conventional conditions in the art or conditions recommended by the manufacturers; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents available from commercial channels such as conventional markets.
[0080] Example 1
[0081] This embodiment discloses a perovskite material layer, the preparation process of which includes the following steps:
[0082] (I) PbBr2 and MABr are dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1.15 to obtain a mixed solution, wherein the volume ratio of DMF and DMSO is 5:1, and the sum of the concentrations of PbBr2 and MABr in the mixed solution is 10 mol / L based on MAPbBr3, and additive monomers A2-1 and B1-1 (the mass ratio of A2-1:B1-1 is 1:1.05) are added to obtain a precursor solution. The mass fraction of the additive monomers (A2-1 and B1-1) is 5% based on the final perovskite MAPbBr3.
[0083]
[0084] (II) After the precursor solution is evenly coated on the ITO glass substrate coated with PEDOT:PSS by spin coating (rotation speed 3000rpm), an anti-solvent and thermal annealing process is immediately performed. Chlorobenzene is used as the anti-solvent, the thermal annealing temperature is 50°C, and the annealing time is 40min. A perovskite material layer with a thickness of 40nm is formed on the surface of the ITO glass substrate coated with PEDOT:PSS.
[0085] This embodiment discloses a perovskite light emitting diode (PeLEDs), the preparation process of which includes the following steps:
[0086] (I) PbBr2 and MABr are dissolved in a mixed solvent of DMF and DMSO at a molar ratio of 1:1.15 to obtain a mixed solution, wherein the volume ratio of DMF and DMSO is 5:1, and the sum of the concentrations of PbBr2 and MABr in the mixed solution is 10 mol / L based on MAPbBr3, and additive monomers A2-1 and B1-1 (the mass ratio of A2-1:B1-1 is 1:1.05) are added to obtain a precursor solution. Compared with the final perovskite MAPbBr3, the mass fraction of the additive monomers (A2-1 and B1-1) is 5%.
[0087] (II) After the precursor solution is evenly coated on an ITO glass substrate coated with PEDOT:PSS (thickness of 50 nm) by spin coating (rotation speed 3000 rpm) (the ITO glass substrate includes an ITO electrode with a thickness of about 50 nm and a glass substrate with a thickness of about 0.5 mm), an anti-solvent and thermal annealing process is immediately performed. Chlorobenzene is used as the anti-solvent, the thermal annealing temperature is 50°C, and the annealing time is 40 minutes. A perovskite material layer with a thickness of 40 nm is formed on the surface of PEDOT:PSS.
[0088] (III) After thermal annealing, a thermal evaporation process is used to sequentially prepare an electron transport layer (TPBi) with a thickness of 30 nm, a lithium fluoride with a thickness of 1 nm, and a layered Al electrode (with a thickness of 100 nm) on the surface of the perovskite material layer to obtain the final PeLEDs device.
[0089] Comparative Example 1
[0090] This comparative example discloses a perovskite light-emitting diode, which is different from Example 1 only in that monomers A2-1 and B1-1 are not added in this comparative example 1.
[0091] Test example
[0092] This test example tests the performance of the perovskite light-emitting diodes obtained in the examples and comparative examples, specifically including:
[0093] (1) The microscopic test results of the perovskite material layer of the diode in Comparative Example 1 and Example 1 are as follows: Figure 1-2 shown.
[0094] (2) The stability test results of the perovskite light-emitting diodes in Example 1 and Comparative Example 1 are as follows: Figure 3-4 The test steps include: placing the device under test in a dark room, using a constant DC voltage of 4V, and an initial test brightness of 900cd / m 2 , record the brightness value every 5 minutes.
[0095] It can be seen that the perovskite material layer prepared by the metal-free catalytic click polymerization additive method of the present invention has a more uniform and dense morphology, and the harmful "pinholes" are basically eliminated. At the same time, under the condition of continuous lighting with an initial brightness of 900 nits in the air, the half-life of the perovskite light-emitting diode prepared by the present invention reaches 40 days (such as Figure 3 As shown). In contrast, the operational stability of the perovskite light-emitting diode that does not use the metal-free catalytic click polymerization additive process of the present invention is greatly reduced, and the half-life is only 165 minutes (as shown Figure 4 As shown). The alkyne-amine click polymerization used in the embodiment of the present invention is a mild click polymerization (40°C), which is very conducive to its full reaction as an additive in the subsequent thermal annealing process of the perovskite light-emitting diode, avoiding the damage of the reaction residue to the photoelectric performance of the perovskite device.
[0096] The present invention proposes a method for in-situ crosslinking of metal-free catalytic click polymerization additives to improve the operational stability of perovskite light-emitting diodes, which is an in-situ crosslinking strategy based on metal-free catalytic click polymerization such as alkyne-amine. The characteristics of metal-free catalytic click polymerization are simplicity, high efficiency, and specificity. At the same time, it is easy to introduce a variety of heteroatoms into the polymer chain to give the prepared polymer material special properties. At the same time, the reaction process does not require a catalyst, which has significant advantages in fields that are sensitive to catalysts, such as optoelectronic devices and biomedicine. Regarding the metal-free catalytic click polymerization in-situ crosslinking strategy of the present invention, specifically:
[0097] 1) The present invention can directly use cross-linkable acetylene monomers and amine monomers as additives to form a continuous network structure through in-situ metal-free catalytic click polymerization, which can effectively block ion migration while protecting grain boundaries and passivating defects, thereby significantly improving the operational stability of PeLEDs.
[0098] 2) The metal-free catalytic click polymerization monomer of the present invention is added to the perovskite precursor solution as an additive, and then processed into a film through the solution together with the perovskite precursor solution, and quickly annealed for 2min-1h at a temperature of 40-80°C, or first vacuum-dried for 1-10min, and then annealed for 1-30min at a temperature of 40-60°C. During the annealing and drying process, the metal-free catalytic click polymerization monomer additive generates a network cross-linked structure in situ. The monomer additive contains atoms with lone pairs of electrons such as O, N, and S, which can effectively interact with perovskite and anchor and enrich at the grain boundaries.
[0099] Among them, the annealing temperature of the perovskite device in the related art usually exceeds 100°C, the purpose is to quickly induce the formation of a large number of crystal nuclei through a higher temperature, so as to achieve a relatively orderly growth of subsequent grains. This places high demands on both equipment and energy consumption, especially considering the large-scale mass production in the future, which will be a huge cost expenditure. The perovskite light-emitting diode of the present invention can achieve an annealing process of 40°C, and the perovskite crystal quality is not attenuated. This is due to the high efficiency of metal-free catalytic click polymerization such as amino-alkyne and its mild reaction temperature (40°C to 50°C). When the temperature reaches 40°C, monomers such as amino-alkyne quickly and efficiently undergo metal-free catalytic click polymerization to form a three-dimensional network structure, and the perovskite precursor liquid is divided into countless small parts in space. The perovskite is bound in this small "grid" and can be slowly crystallized to form a dense perovskite film with relatively uniform grain size. The perovskite film prepared by the present invention has uniform thickness, dense and uniform surface morphology, and the performance of the corresponding perovskite light-emitting diode device remains unchanged. At the same time, the cross-linked polymers formed by metal-free click polymerization of monomers such as amino-alkyne described in the present invention fully fill the gaps between the perovskite grains, achieving tight wrapping and protection of the perovskite grains. The mild annealing temperature greatly reduces the difficulty and complexity of the process, while increasing the thermal stability selection window of the available materials.
[0100] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values 2 and 3.
[0101] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A polymer additive, characterized in that It includes a cross-linked polymer formed by a click polymerization reaction of monomers after being added to the raw materials for preparing perovskite, wherein the type of click polymerization reaction includes at least one of amino-alkynyl click polymerization, thiol-alkynyl click polymerization, thiol-alkynyl click polymerization, hydroxyl-alkynyl click polymerization, and Diels-Alder click polymerization.
2. The polymer additive according to claim 1, characterized in that The monomer includes an acetylene compound I with a functionality of 2 or more and an amine compound II with a functionality of 2 or more, and the sum of the functionalities of the acetylene compound I and the amine compound II is 5 or more; or / and, the monomer includes a monomer compound III containing both an acetylene group and an amine group, and the sum of the functionalities of the acetylene group and the amine group in the monomer compound III is 3 or more; Preferably, the functionality of the acetylene compound I is 3 or more, and the functionality of the amine compound II is 2 or more; or, the functionality of the acetylene compound I is 2 or more, and the functionality of the amine compound II is 3 or more; Preferably, the acetylene compound I is a trifunctional acetylene compound, and the amine compound II is a difunctional amine compound; or, the acetylene compound I is a difunctional acetylene compound, and the amine compound II is a trifunctional amine compound; Preferably, the monomer compound III includes more than 2 amine groups and more than 3 alkynyl groups, or the monomer compound III includes more than 3 amine groups and more than 2 alkynyl groups.
3. The polymer additive according to claim 2, characterized in that The acetylene compound I comprises at least one of the following compounds: Wherein, R1 and R2 are independently selected from C1 to C 10 Alkyl, C1~C 10 Alkoxy; p, q, r, t are all integers, and p is selected from 2 to 20, q and r are independently selected from 0 to 8 each time they appear, and t is independently selected from 2 to 10 each time it appears; Preferably, R1 and R2 are independently selected from C1-C5 alkyl and C1-C5 alkoxy; Preferably, said R1 and R2 are independently selected from methyl, ethyl or propyl.
4. The polymer additive according to claim 2, characterized in that The amino compound II includes at least one of the following compounds: Wherein, each occurrence of R3 is independently selected from C1 to C 10 Alkyl, C1~C 10 Alkoxy; m, n, k, s, w are all integers, and m and n are independently selected from 2 to 8 at each occurrence, k is independently selected from 2 to 6 at each occurrence, s is independently selected from 0 to 8 at each occurrence, and w is independently selected from 2 to 18 at each occurrence; Preferably, the compound B6 comprises at least one of the following compounds:
5. The polymer additive according to claim 2, characterized in that The monomer compound III includes at least one of the following compounds: a and b are both integers, and each occurrence of a and b is independently selected from 0 to 8.
6. A method for preparing the polymer additive according to claim 1, characterized in that: The method comprises the following steps: mixing an additive preparation raw material containing a monomer and a solvent with a perovskite preparation raw material, heating, and performing a click polymerization reaction to obtain a polymer additive; Preferably, the heating temperature is 40-100° C.; or / and, the heating time is 5-300 min; Preferably, the raw materials for preparing the additive are the monomer and the solvent.
7. A perovskite material, characterized in that: The invention comprises the polymer additive according to any one of claims 1 to 5 or the polymer additive prepared by the preparation method according to claim 6.
8. A method for preparing the perovskite material according to claim 7, characterized in that: The method comprises the following steps: taking a raw material for preparing perovskite and a raw material for preparing a polymer additive containing a monomer and a solvent, mixing them, and annealing them to obtain the perovskite material; Preferably, the solvent comprises N,N-dimethylformamide and dimethyl sulfoxide; or / and, the annealing temperature is 40-100°C; or / and, the annealing time is 5-300 min; or / and, the raw materials for preparing the perovskite comprise PbX2 and BX, wherein X is independently selected from at least one of F, Cl, Br or I each time it appears; B is selected from at least one of MA, FA or Cs; Preferably, the preparation method comprises: S1, mixing a raw material for preparing perovskite, a monomer and a solvent to obtain a mixture; S2, coating the mixture on a substrate surface and annealing to obtain the perovskite material.
9. A photoelectric device, characterized in that: Including the perovskite material according to claim 7 or the perovskite material prepared by the preparation method according to claim 8.
10. Use of the polymer additive according to any one of claims 1 to 5, or the polymer additive prepared by the preparation method according to claim 6, or the perovskite material according to claim 7, or the perovskite material prepared by the preparation method according to claim 8 in the preparation of optoelectronic devices.
Citation Information
Patent Citations
Polytriazole with intrinsic flame retardance and preparing method and application thereof
CN105906807A
Perovskite thin film additive, perovskite thin film preparation method and application thereof
CN110707214A
Preparation method of spindle-shaped perovskite CsPbBr3 micron particles
CN111573716A
Preparation method of CsPbBr3 spindle type perovskite micro-particles with adjustable size
CN111592035A
Method for preparing perovskite thin film based on additive engineering and photoelectric application thereof
CN112582544A